2011
DOI: 10.4028/www.scientific.net/amm.66-68.907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liquid Oxidation Surface Treatment on Bonding Properties of Wood/Polyethylene Composites

Abstract: In this paper the surface of wood/polyethylene (PE) composites were treated by liquid oxidation, and the structure of surface for wood/polyethylene composites before and after treatment was characterized by contact angle, fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM); combined with bonding strength test, the effect of concentration for handling solution and addition of oxidant on bonding properties of wood/polyethylene composites was also investigated. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A decrease in the contact angle resulted in better surface wettability. The work of Teng et al [14] showed that the chromic treatment reduced the contact angle for wood-HDPE composites, and Moghadamzadeh et al [15] noted a decrease in the contact angle from 83 to…”
Section: Effect Of Chromic Treatment On Contact Anglementioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in the contact angle resulted in better surface wettability. The work of Teng et al [14] showed that the chromic treatment reduced the contact angle for wood-HDPE composites, and Moghadamzadeh et al [15] noted a decrease in the contact angle from 83 to…”
Section: Effect Of Chromic Treatment On Contact Anglementioning
confidence: 99%
“…Teng et al [14] demonstrated that the surface of the wood/polyethylene composites decreased and the surface's wettability improved after liquid oxidation; the functional groups -C-O-and C=O were formed on the treated surface, and the surface roughness increased. Thus, after treatment, the shear bond strength of the treated sample increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…However, knowledge of the surface properties of the composite is essential for the development of a suitable coating system. Teng et al [21] demonstrated that the contact angle of the surface of wood/polyethylene composites decreased. The surface's wettability improved after liquid oxidation and led to the formation of -C-O-and C=O functional groups on the treated surface, and the surface roughness increased.…”
Section: Introductionmentioning
confidence: 99%
“…A greater number of studies have addressed the use of corona and plasma treatments for WPC materials [10,12,15,16,17,18] than have investigated mechanical [10,15] or flame [15,19] or chemical [10,12,20] treatments for WPCs. Plasma and flame treatment options are suitable for use in factory production, however many WPC applications utilise relatively low investment technology, and a workshop scale of production.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its relatively high cost epoxy resin is a less commonly used adhesive for wood jointing in furniture industry [21], however it is widely used for polymer composites. Many researchers [10,15,19,20] have used epoxy resin as the adhesion system for studies on WPC materials. A preliminary study on WPC materials [22] had compared lap shear strength of epoxy with the more traditional wood glues: PVA and polyurethane.…”
Section: Introductionmentioning
confidence: 99%